Literature Study on the Effect of Price, Facilities, and Service Quality on Airline Customer Satisfaction - Reza Pribadi, Mochamad (Dinasti International Journal of Digital Business Management, 2024)
Aviation is one of the important industrial sectors in the global economy, so it is important to understand what factors affect customer satisfaction in the aviation industry. The effect of price, facilities, and service quality on customer satisfaction is a scientific article of literature study within the scope of the aviation field. The purpose of this article is to build hypotheses about the effect of price, facilities, and service quality on airline customer satisfaction for future research. Research objects on online libraries, Google Scholar, Mendeley and other academic online media related to the influence of price variables, facilities, and service quality on customer satisfaction. The research method library research and systematic literature review (SLR) sourced from e-books and open access e-journals. The analysis method is qualitative descriptive analysis. The results of this article indicate that the hypotheses that can be built for further research are: 1) price affects airline customer satisfaction; 2) facilities affect airline customer satisfaction; and 3) service quality affects airline customer satisfaction.